2021
DOI: 10.2147/ijgm.s298517
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Benign Ground-Glass Nodules: CT Features and Pathological Findings

Abstract: Background: Some pulmonary ground-glass nodules (GGNs) are benign and frequently misdiagnosed due to lack of understanding of their CT characteristics. This study aimed to reveal the CT features and corresponding pathological findings of pulmonary benign GGNs to help improve diagnostic accuracy. Patients and Methods: From March 2016 to October 2019, patients with benign GGNs confirmed by operation or follow-up were enrolled retrospectively. According to overall CT manifestations, GGNs were classified into thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
(27 reference statements)
1
16
0
Order By: Relevance
“…Unlike inflammatory PSNs, we found that the solid component in malignant PSNs predominantly appeared as an irregular shape with a scattered or eccentric distribution, which was consistent with previous results. 25–28 We also found that the intra-nodular vessel sign which could be evaluated only in SSNs was frequently observed in both groups, which was in agreement with the findings of Gao et al 3 and Fu et al 29 who showed that intra-nodular vessels can be observed in both inflammatory and malignant nodules. Furthermore, Gao et al 3 , 30 indicated that abnormal changes of the blood vessels passing through the nodules are highly suggestive of malignancy.…”
Section: Discussionsupporting
confidence: 92%
“…Unlike inflammatory PSNs, we found that the solid component in malignant PSNs predominantly appeared as an irregular shape with a scattered or eccentric distribution, which was consistent with previous results. 25–28 We also found that the intra-nodular vessel sign which could be evaluated only in SSNs was frequently observed in both groups, which was in agreement with the findings of Gao et al 3 and Fu et al 29 who showed that intra-nodular vessels can be observed in both inflammatory and malignant nodules. Furthermore, Gao et al 3 , 30 indicated that abnormal changes of the blood vessels passing through the nodules are highly suggestive of malignancy.…”
Section: Discussionsupporting
confidence: 92%
“…The extraction of radiomics parameters was set as follows: image resampling parameters: 2 × 2 × 2 and binWidth: 64. A total of 47 parameters were extracted, including First Order Statistics, 10 Shape, 5 Gray Level Cooccurrence Matrix, 7 Gray Level Run Length Matrix, 11 Gray Level Size Zone Matrix, 11 and Neighboring Gray Tone Difference Matrix. 3…”
Section: Methodsmentioning
confidence: 99%
“…The characterization of CT features of benign nodules was reported in a recent retrospective study on 79 patients with GGNs. Some common CT manifestations were identified, including a regular or irregular nodule with an isolated, blurred internal high-attenuation zone connecting to the blood vessels, or a nodule abutting but not surrounding blood vessels, suggesting that follow-up should be firstly considered for GGNs with these characteristics for a higher likelihood of benignity ( 17 ).…”
Section: Benign Vs Malignant Ground-glass Nodulesmentioning
confidence: 99%
“…Most guidelines highly recommend an imaging reassessment within 3 months’ time after first detection of GGN with a size above 10 mm, while a reassessment within 6–12 months’ time is recommended for GGN above 5 mm. This is because mean resolve time of transient GGNs appears to be 4.8 months and most GGNs disappeared within 3 months ( 17 ). The Lung-RADS recommended that the strategy for follow-up of pGGN depends on the size of the nodules.…”
Section: Treatment Follow-up and Clinical Outcomesmentioning
confidence: 99%